Evaluation of Toll-Like Receptor 2 and 4 RNA Expression and the Cytokine Profile in Postmenopausal Women with Metabolic Syndrome - Orsatti, Claudio Lera [UNESP]; Nahás, Eliana Aguiar Petri [UNESP]; Nahas-Neto, Jorge [UNESP]; Orsatti, Fabio Lera; Giorgi, Vanessa Innocenti [UNESP]; Witkin, Steven Sol [UNESP] (Public Library Science, 2014)
Objective: To evaluate the gene expression of Toll-Like (TLR-2 and TLR-4) receptors and cytokine profile in postmenopausal women with or without metabolic syndrome (MetS).Methods: In this cross-sectional study, 311 Brazilian women (age >= 45 years and amenorrhea >= 12 months) were included. Women showing three or more of the following diagnostic criteria were diagnosed as positive for MetS: waist circumference>88 cm, triglycerides >= 150 mg/dL, HDL cholesterol<50 mg/dL, blood pressure >= 130/85 mmHg, and fasting glucose >= 100 mg/dL. The expression of TLR-2 and TLR-4 in peripheral blood was evaluated by RNA extraction and subsequent real time PCR analysis. The cytokine profile, tumor necrosis factor alpha (TNF-alpha) and interleukins 1 beta, 6, and 10, were measured by ELISA.Results: The expression of TLR-2 RNA was demonstrated in 32.5% and TLR-4 in 20.6% of the subjects. There was no association between the expression of TLR-2 and TLR-4 and the presence or absence of MetS (P>0.05). A greater production of IL-6 was associated with TLR-2 and TLR-4 expressions and greater production of TNF-alpha was associated only with TLR-2 expression (P>0.05). Only the lower quartile of IL-10 was associated with the presence of the MetS (P>0.05).Conclusions: TLR-2 and TLR-4 expressions were associated with increased pro-inflammatory cytokines, IL-6 and TNF-alpha, with no association with biomarkers of MetS. The low concentrations of IL-10 may suggest an anti-inflammatory modulation in postmenopausal women with MetS.